Sustainable agricultural development for food security and nutrition: What roles for livestock? A report by the High Level Panel of Experts on Food Security and Nutrition of the Committee on World Food Security - High Level Panel of Experts on Food Security and Nutrition (Food and Agriculture Organization of the United Nations, 2016)
This report addresses the economic, environmental and social dimensions of agricultural development, with the objective of ensuring food and nutrition security, in terms of availability, access, utilization and stability. It focuses on the livestock component of agricultural systems, given the role of livestock as an engine for the development of the agriculture and food sector, and as a driver of major economic, social and environmental changes in food systems worldwide. The report identifies challenges to the achievement of sustainability in livestock systems and possible pathways towards sustainable agricultural development that contribute to current and future food security and nutrition. The report concludes with recommendations for appropriate actions by policy-makers and stakeholders.